Role of magnetic resonance imaging in prediction of outcome in traumatic diffuse axonal injury: A single-centre observational study - Thulung, Suraj; Yogi, Nikunj (Nepal Journal of Neuroscience, 2021)
Introduction: Incidence of diffuse axonal injury has been estimated at 40-50% of hospitalizations. Recently, much interest has been directed towards the potential of newer imaging sequences of magnetic resonance imaging to investigate diffuse axonal injury (DAI) and to prognosticate the outcome. In this study, we correlated the magnetic resonance imaging grades of diffuse axonal injury with clinical outcome in terms of Glasgow Outcome Scale (GOS). Methods and Materials: A hospital based observational study was carried out at Upendra Devkota Memorial National Institute of Neurological and Allied Sciences, Kathmandu in 69 patients of diffuse axonal injury between November 2017 to November 2018. Data was collected on patient and trauma characteristics, as well as neurological assessment and MRI findings. Outcome was assessed as favourable and unfavourable GOS for various MRI grades of diffuse axonal injury. Results: There were 21.74%, 42.03% and 36.23% of cases with grade I, II and III diffuse axonal injury respectively. There were 0 (0%), 2 (11.8%) and 15 (88.2%) cases of MRI grade I, II and III diffuse axonal injury in favourable GOS group and 15 (28.8%), 27 (51.9%) and 10 (19.2%) cases of MRI grade I, II and III diffuse axonal injury in unfavourable GOS group (p=0.00). Conclusion: This study showed that there was a significantly higher chance of unfavourable outcome with increasing MRI grades of diffuse axonal injury.